Geniş alan görüntülerinde anomali tespiti - Şahin, Abdullah Hamza; Ateş, Hasan Fehmi; Güntürk, Bahadır Kürşat (Institute of Electrical and Electronics Engineers Inc., 2021)
Bu çalışma hava araçlarından çekilmiş geniş alan görüntülerindeki anomalileri tespit etmek ile ilgilidir. Anomali kümesi normal seyrin dışındaki her şey olarak belirlenmiştir. Bu amaçla iki farklı veri seti kullanılmış ve deneyler bu veri kümelerinin üzerinde yapılmıştır. Anomali tespiti için geçmiş görüntüleri kullanarak bir sonraki görüntüyü oluşturmaya çalışan bir evrişimli sinir ağı modeli tasarlanmıştır. Görüntüler modele verilmeden önce ön işlemeden geçirilmiştir. Tahmin edilen görüntü ve gerçek olan görüntü karşılaştırılarak anomali tespiti yapılmıştır.

This study is about detecting anomalies in wide area imagery collected from an aircraft. The set of anomalies have been identified as anything out of the normal course of action. For this purpose, two different data sets were used and the experiments were carried out on these data sets. For anomaly detection, a convolutional neural network model that tries to generate the next image using past images is designed. The images were pre-processed before being given to the model. Anomaly detection is performed by comparing the estimated image and the true image.
Anomaly detection in wide area imagery
Keywords: Anomali Tespiti; Evrişimsel Sinir Ağları; Derin Öğrenme; Bilgisayarla Görü; Anomaly Detection; Convolutional Neural Networks; Deep Learning; Computer Vision